Clinical outcomes of platinum-based chemotherapy according to T790M mutation status in EGFR-positive non-small cell lung cancer patients after initial EGFR-TKI failure. (July 2017) - Yoshida, Tatsuya; Kuroda, Hiroaki; Oya, Yuko; Shimizu, Junichi; Horio, Yoshitsugu; Sakao, Yukinori; Hida, Toyoaki; Yatabe, Yasushi
Highlights: We evaluated the efficacy of platinum-based chemotherapy according to the EGFR T790M status. We retrospectively reviewed 50 EGFR-positive NSCLC patients after EGFR-TKIs failure. There were no differences in the efficacy of platinum-based chemotherapy according to the T790M. Abstract: Background: Emergence of the T790M point mutation in exon 20 of epidermal growth factor receptor ( EGFR ) is the most common mechanism of resistance to EGFR tyrosine kinase inhibitors (EGFR-TKIs). It remains unclear whether the efficacy of platinum-doublet chemotherapy is impacted by the presence of the T790M mutation. The aim of this study is to evaluate the efficacy of platinum-doublet chemotherapy after initial EGFR-TKI failure according to the EGFR T790M in patients with advanced EGFR -mutation-positive non-small cell lung cancer (NSCLC). Patients and methods: We retrospectively reviewed 50 patients with advanced NSCLC harboring EGFR mutations who underwent rebiopsy to evaluate their T790M mutation status after development of resistance to first-line EGFR-TKIs (gefitinib, erlotinib, or afatinib) and were subsequently treated with second-line platinum-based chemotherapy. Results: The median age of patients was 63 years (range, 35–77 years), and 15 (30%) patients were male. Histological examination revealed that all patients had adenocarcinoma, 39 (78%) had stage IV disease, and 11 (22%) patients had postoperative recurrence. Of all, 17 patients (34%) had the T790M mutation by rebiopsy after initial EGFR-TKI failure. The overall response rate (ORR) of platinum-doublet chemotherapy was 24% for both T790M-positive and T790M-negative patients. There was no significant difference in the progression-free survival (PFS) in T790M-positive and T790M-negative patients (median PFS, 6.0 months vs. 5.1 months; 95% confidence interval [CI], 0.1–11.9 vs. 4.4–5.8; hazard ratio [HR], 0.90 [95%CI, 0.49–1.66]; P  = 0.7210). None of the factors were predictive of platinum-doublet chemotherapy efficacy by the multivariate analysis. Conclusion: There were no differences in clinical outcomes of platinum-based chemotherapy according to the T790M status of NSCLC patients.